Environment-friendly dual-network hydrogel dust suppressant based on xanthan gum, polyvinyl alcohol and acrylic acid. (1st October 2021) - Wei, Jianfeng; Zhao, Yanyun; Yu, Shijian; Du, Jianhua; Hu, Xiangming; Bai, Guangxing; Wang, Zhaoxi
Abstract: Hydrogen bonding interactions among poly vinyl alcohol (PVA), xanthan gum (XG) and acrylic acid (AA) molecules have been utilized to prepare an environment-friendly interpenetrating double-network hydrogel dust suppressant (PVA-XG-PAA/SDBS) with the aim of enhancing the poor mechanical performance of current hydrogel dust suppressants. A single factor test was used to determine the optimal formulation conditions for the PVA-XG-PAA/SDBS, and the viscosity, surface tension, compression strength, wind resistance, water retention and biodegradability of the samples were measured. The results showed that the hydrogel with optimal usage contained 1.5 g, 0.1 g, and 6 g of PVA, XG and AA, respectively and the optimal reaction temperature was 55 °C. Under the optimal conditions, the viscosity was 45 mPa s, the surface tension was 30 mN/m, the compression strength of the dust suppressant-solidified coal pillar reached 126 kPa, and the degradation rate at the 8th cycle (40 days) after being buried in soil was 34%. Compared with a conventional hydrogel dust suppressant, like poly acrylic acid (PAA), and the dust suppressant sodium dodecyl benzene sulfonate (SDBS), the PVA-XG-PAA/SDBS showed better water retention, wind erosion resistance, and dust-solidifying properties. On the basis of these remarkable properties, the PVA-XG-PAA/SDBS is applicable for dust prevention during coal mining, transport, and storage, which enhances the dust suppression efficiency obviously and has significant meaning to the sustainable development of the coal mining industry while protecting the environment. Graphical abstract: Image 1 Highlights: Preparation of a hydrogel dust suppressant with interpenetrating double-network structure. The dust suppressant bonds coal dust together to form a high-strength solidified film. The dust suppressant is environmentally friendly.